How much do you love Pakistan: A property tax revenue simulation for a municipal revolution in Punjab - Aziz, Daniyal; Haider, Sabieh; Raja, Muhammad Nasim Khan (International Food Policy Research Institute, 2014)
Governance Institutes Network International (GINI) entered into agreement as a collaborating institution with the International Food Policy Research Institute (IFPRI) to conduct property tax policy research to support the 2011 “Framework for Economic Growth” developed by the Planning Commission of Pakistan at that time. Over the course of this 12-month project, spanning between 1st July 2012 and 30th June 2013, GINI conducted empirical tax policy research on property taxation primarily focused on Tehsil Shakargarh, District Narowal of Punjab Province.